Effect of Supplementing Azolla microphylla on Feed Intake and Blood Parameters in Growing Crossbred Female Calves - Khare, Arbind; Chatterjee, A.; Mondal, M.; Karunakaran, M.; Ghosh, M.K.; Dutta, T.K. (Indian Journal of Animal Nutrition, 2018)
A study was conducted on 12 crossbred female calves distributed into two groups to assess the effect of supplementing Azolla microphylla on feed intake and blood parameters. The animals in group T0 were fed with conventional ration consisting of paddy straw and concentrate mixture in 1: 1 ratio. In group T1, fresh Azolla microphylla was supplemented @ 1.5 kg/animal (equivalent to 90 g DM) replacing equivalent weight of concentrate mixture on DM basis. The feed intake was similar in both the groups, however, growth rate was better (P